If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10(2a + -3b) + -1(4b + -2a) = 0 (2a * 10 + -3b * 10) + -1(4b + -2a) = 0 (20a + -30b) + -1(4b + -2a) = 0 Reorder the terms: 20a + -30b + -1(-2a + 4b) = 0 20a + -30b + (-2a * -1 + 4b * -1) = 0 20a + -30b + (2a + -4b) = 0 Reorder the terms: 20a + 2a + -30b + -4b = 0 Combine like terms: 20a + 2a = 22a 22a + -30b + -4b = 0 Combine like terms: -30b + -4b = -34b 22a + -34b = 0 Solving 22a + -34b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '34b' to each side of the equation. 22a + -34b + 34b = 0 + 34b Combine like terms: -34b + 34b = 0 22a + 0 = 0 + 34b 22a = 0 + 34b Remove the zero: 22a = 34b Divide each side by '22'. a = 1.545454545b Simplifying a = 1.545454545b
| 19-4+5-16= | | 3-8x-16x^4=0 | | (3x/4)=2 | | 3x+5yi=8-i | | f(x)=tan(cos(2x)) | | (5x/6)=0 | | 5/3x=2/3x+1/3 | | -1/8z=-5.5 | | x+14=171 | | (-3/5)m=12 | | hj-2h+5g+4f-20= | | 3y-4=6 | | -16x^2-7x+10=0 | | 2.38=48 | | -16x^2-7x-1=0 | | 5(2w+3)10w=6(4w+1) | | 4+-2v+12=-8 | | x^2-36/2x-12 | | 2(1+3s)-4=6s-2 | | d=3m | | 6+3+2+2= | | (-b/3)=6 | | 5-(f+3)=5f | | 91=-4(6-6b)-5 | | 2ln(x)=ln(21) | | 17=32 | | 40=16t^2+88t | | 20=(1/4c) | | 75=3x^2-9 | | 18x+5=20x+1 | | log*(x+11)-log(2)=log*(5x+1) | | 21=-7u |